(untitled) (Physical Education, Health and Social Sciences, 2025)
Obesity is recognized as a root cause of various diseases and can significantly affect renal functional levels, leading to further complications in metabolic and hepatic health. Overweight and obese young women are more likely to become overweight or obese adults, putting them at higher risk for serious health conditions such as type 2 diabetes, renal diseases, and hypertension risks which are linked to alterations in serological parameters. This prospective study investigated selected serological parameters among young university-going girls aged 18–25 years in Narowal, Pakistan. A total of = 400) were included in this study, which were further divided into the Control Group and Experimental Groups (i.e., underweight, overweight, and Obese) based on BMI. Anthropometric measurements were conducted, and blood samples were collected to analyze serum creatinine and serum urea levels using an automated chemistry analyzer. The results demonstrated significant differences (P<0.006) in both serum creatinine and urea levels across the different weight categories. Specifically, serum creatinine and urea levels were positively correlated with participants who were underweight, overweight, or obese, while a positive correlation was observed in those with a normal weight. The findings highlighted the increasing prevalence of obesity among young adults in Pakistan, which is a growing public health concern. In conclusion, body weight is closely associated with important biochemical indicators. Changes in these parameters can lead to significant health issues, underscoring the need for effective interventions targeting young adults to prevent long-term health complications.